Impact of lecithin incorporation on gel properties of bigeye snapper (Priacanthus tayenus) surimi. (18th November 2020) - Panpipat, Worawan; Cheong, Ling‐Zhi; Chaijan, Manat
Summary: Gelling characteristics of bigeye snapper ( Priacanthus tayenus ) surimi functionalised by lecithin at different concentrations were investigated. Lecithin at ≤1 g 100 g −1 had no impact on breaking force and deformation ( P > 0.05). Expressible drip tended to decrease with increasing lecithin level up to 1 g 100 g −1 . Lecithin at 1–3 g 100 g −1 improved the whiteness ( P < 0.05). Jointed clusters were formed in the gel microstructure with 1 g 100 g −1 lecithin. Gel without and with 1 g 100 g −1 lecithin had the same texture profile and likeness scores (texture, odour and flavour) ( P > 0.05). Peroxide value, TBARS content and rancid odour score of gels were changed considerably during refrigerated storage (4 °C/polyethylene bag) for 15 days but lower values of all indices were noticeable in gel with lecithin. Therefore, lecithin at 1 g 100 g −1 was the optimum concentration for stabilising the texture, improving the water holding capacity, whitening the colour and retarding the lipid oxidation of bigeye snapper surimi gel. Abstract : Impact of lecithin incorporation on gel properties of bigeye snapper ( Priacanthus tayenus ) surimi.